Image Video Teaching Method in College Physical Education - Haibo Xu; Lun Wan (Applied Bionics and Biomechanics)
At present, traditional methods of physical education in colleges and universities are no longer able to meet the requirements of modern physical education and need to be improved. The application of the visual teaching method to the teaching of physical education in college in the classroom can best see the modern theory of physical education, which is necessary for the theory of physical education in college. On this basis, it is recommended to use the teaching method with image in the teaching of physical education in college. This document is in the form of a search query in conjunction with other search methods to perform a search. This article takes Tai Chi in the university physical education curriculum as an example. It selects two classes with no difference in number of genders and conducts traditional teaching and VR image video teaching, respectively. And from the learning situation, interest and satisfaction of the two classes analyze the degree. In this study, we found that before the experiment, the number of students with 85 scores or above in the control class was 8, accounting for 20%, 14 students with 70-85 scores, accounting for 35%, and 18 students with 60-70 scores, accounting for 45%. As could be observed, the majority of students in the control class scored between 60 and 70 points overall, with a merit rate of only 55%. In the experimental class, there are 15 students with 85 points or above, accounting for 37.5%, 18 students with 70-85 points, accounting for 45%, and 7 students with 60-70 points, accounting for 17.5%. In the experimental class, the overall score of students is between 70 and 85 points, accounting for 82.5%. The image and video teaching method can be seen to be useful in improving students’ athletic achievement. In addition, the image and image instruction approach can better enhance students’ interest in learning, and most students are satisfied with the image and video instruction approach.